Anima e corpo: le politiche del corpo e della femminilità in Ama Ata Aidoo e Paulina Chiziane (Altre Modernità, 2019)
Women too are the protagonists of a paramount history of slavery. In innumerable geographies around the world and at different levels of subjection, women have been living in a state of servitude imposed, in the very first place, by their own families. The mechanisms of “tradition” have always pushed them to restrain their necessities and requests, teaching them to devote themselves to “the Other” − who could be the husband, the children, the parents, the whole family, etc. But what would happen if these women raised their voices against this system, finally encouraging a change? Within the context of Sub-Saharian Africa, two female authors give us some possible answers: Ghanaian Ama Ata Aidoo (1942) with her novel Changes: A Love Story (1991), and Mozambican Paulina Chiziane (1955) with her Niketche: Uma História de Poligamia (2002). The main characters of both narrations (and, through them, the authors themselves) lay claim to their right to bodily pleasures and to the exercise of a free sexuality. This eventually paves the way to a full authority on their body and, therefore, on their whole being. Our analysis of sexuality will combine the literary perspective of these two Black African female authors with Judith Butler’s performativity and body theory; (Black) African feminist theories by Oyeronke Oyewumi, Mary Kolawole, and Sylvia Tamale; and Audre Lorde’s “joy of body”.
Keywords: Ama Ata Aidoo; Paulina Chiziane; African feminism/s; female African authorship; female Black body